A multiplex PCR for differential detection of Echinococcus granulosus sensu stricto, Echinococcus multilocularis and Echinococcus canadensis in China - Shang, Jing-Ye (Infect Dis Poverty, 2019)
BACKGROUND: Echinococcosis caused by Echinococcus is one of the most major infectious diseases in north-west highland of China. E. granulosus sensu strict, E. multilocularis, and E. canadensis are known to be the only three species related to human health transmitting in the areas. To achieve targeted treatment and control of echinococcosis, the accurate identification and discrimination of the species are important. However, currently the available diagnostic approaches do not present ideal results either in accuracy or efficiency. METHODS: In the study, a set of primers were designed to aim at the three human-pathogenic Echinococcus species in China. The one-step multiplex PCR assay was developed and evaluated for the specificity and sensitivity. A total of 73 parasitic lesions and 41 fecal materials obtained from human and various animals collected in the clinic and the field were tested to assess the applicability of this method. RESULTS: The multiplex PCR effectively detected the individual DNA from the targeted species and their random mixtures generating with distinguishable expected size of products. The detection limit of the assay for each of the three species was 5 pg/μl when they were tested separately. When DNA mixtures of the targeted species containing the same concentration were used as templates, the lowest amount of DNA which can be detected was 50 pg/μl, 10 pg/μl and 5 pg/μl for E. granulosus s. s., E. multilocularis, and E. canadensis respectively. No cross-reactivity was observed when DNA from eight genetically close species was used as control templates. The multiplex PCR identifications of all samples were in line with the original sequencing results except for those infected with E. shiquicus, which showed negative signals in the developed assay. Of all the tested stool materials, 16 were previously found positive for Echinococcus by visual and microscopic examination. Among these 16 samples, 13 were confirmed by the multiplex PCR, and the other three tested negative. Additionally, the multiplex PCR identified another 14 positive feces from the remained 25 stool samples which absence of worms. CONCLUSIONS: The developed multiplex PCR shows advantages in fast diagnosis and large-scale epidemiological investigation, which proven to be a promising tool utilized in clinic and surveillance system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40249-019-0580-2) contains supplementary material, which is available to authorized users.